Asciminib in Newly Diagnosed Chronic Myeloid Leukemia - Hochhaus, Andreas; Wang, Jianxiang; Kim, Dong-Wook; Kim, Dennis Dong Hwan; Mayer, Jiri; Goh, Yeow-Tee; le Coutre, Philipp; Takahashi, Naoto; Kim, Inho; Etienne, Gabriel; Andorsky, David; Issa, Ghayas C; et al. (The New England journal of medicine, 2024)
BACKGROUND: Patients with newly diagnosed chronic myeloid leukemia (CML) need long-term therapy with high efficacy and safety. Asciminib, a BCR::ABL1 inhibitor specifically targeting the ABL myristoyl pocket, may offer better efficacy and safety and fewer side effects than currently available frontline ATP-competitive tyrosine kinase inhibitors (TKIs). METHODS: In a phase 3 trial, patients with newly diagnosed CML were randomly assigned in a 1:1 ratio to receive either asciminib (80 mg once daily) or an investigator-selected TKI, with randomization stratified by European Treatment and Outcome Study long-term survival score category (low, intermediate, or high risk) and by TKI selected by investigators before randomization (including imatinib and second-generation TKIs). The primary end points were major molecular response (defined as BCR::ABL1 transcript levels ≤0.1% on the International Scale [IS]) at week 48, for comparisons between asciminib and investigator-selected TKIs and between asciminib and investigator-selected TKIs in the prerandomization-selected imatinib stratum. RESULTS: A total of 201 patients were assigned to receive asciminib and 204 to receive investigator-selected TKIs. The median follow-up was 16.3 months in the asciminib group and 15.7 months in the investigator-selected TKI group. A major molecular response at week 48 occurred in 67.7% of patients in the asciminib group, as compared with 49.0% in the investigator-selected TKI group (difference, 18.9 percentage points; 95% confidence interval [CI], 9.6 to 28.2; adjusted two-sided P<0.001]), and in 69.3% of patients in the asciminib group as compared with 40.2% in the imatinib group within the imatinib stratum (difference, 29.6 percentage points; 95% CI, 16.9 to 42.2; adjusted two-sided P<0.001). The percentage of patients with a major molecular response at week 48 was 66.0% with asciminib and 57.8% with TKIs in the second-generation TKI stratum (difference, 8.2 percentage points; 95% CI, -5.1 to 21.5). Adverse events of grade 3 or higher and events leading to discontinuation of the trial regimen were less frequent with asciminib (38.0% and 4.5%, respectively) than with imatinib (44.4% and 11.1%) and second-generation TKIs (54.9% and 9.8%). CONCLUSIONS: In this trial comparing asciminib with investigator-selected TKIs and imatinib, asciminib showed superior efficacy and a favorable safety profile in patients with newly diagnosed chronic-phase CML. Direct comparison between asciminib and second-generation TKIs was not a primary objective. (Funded by Novartis; ASC4FIRST ClinicalTrials.gov number, NCT04971226).
Keywords: senioři; bcr-abl fúzní proteiny; senioři nad 80 let; Niacinamide; niacinamid; výsledek terapie; Fusion Proteins, bcr-abl; Imatinib Mesylate; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; Kaplanův-Meierův odhad; Adult; mladý dospělý; Antineoplastic Agents; Aged, 80 and over; Young Adult; inhibitory tyrosinkinasy; ženské pohlaví; Pyrazoles; protinádorové látky; Humans; chronická myeloidní leukemie; imatinib mesylát; Tyrosine Kinase Inhibitors; lidé středního věku; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; pyrazoly; dospělí; Female; Aged; Treatment Outcome; lidé; Male